An interactive multi-criteria spatial decision support system for energy retrofitting of building stocks using CommuntiyVIZ to support urban energy planning. (October 2019) - Torabi Moghadam, Sara; Lombardi, Patrizia
Abstract: A major concern for any city is urban energy planning, which is particularly multi-sectoral and multi-actor oriented. This concern is especially critical for the built-up urban zones, which are predominantly responsible for the bulk of energy consumption and carbon emissions. Hence, an interdisciplinary, integrated approach is needed to address this complex challenge. This study focuses on both energy retrofit interventions for existing building stocks and the integration of participative processes in decision-making. It deals with the development of a stakeholder-oriented approach to implementing effective strategies in urban energy planning. This can help define meaningful building energy retrofitting scenarios that focus on energy consumption and environmental impact, in addition to economic and social considerations. A major outcome of this study is the development of a new multicriteria spatial decision support system (MC-SDSS) that is an interactive energy-related plug-in for a geographic information system (GIS) environment, adapted from CommunityViz. The methodology used to deliver the tool can be applied to other contexts and situations due to its flexibility. The new MC-SDSS facilitates the decision-making process for stakeholders who ask "what if" questions and visualise "if-then" scenarios in real time to handle the entire planning procedure adequately. Highlights: A new interactive MC-SDSS is proposed for energy retrofitting of building stocks. Multiple criteria were assessed to measure the impact of retrofit scenarios. Results were tested through a participatory workshop involving stakeholders. The MC-SDSS facilitates the decisional process for stakeholders in real-time.